Moderasi GCG dan Leverage terhadap Pengaruh Ukuran Perusahaan pada Tax Avoidance - Intan Sri Devi, Dewa Ayu; Bagus Dwirandra, A.A. Ngurah (E-Jurnal Akuntansi; Vol 30 No 10 (2020)DO - 10.24843/EJA.2020.v30.i10.p11, 2020)
The size of the company has a positive effect on Tax Avoidance but it is suspected that it is not always linear due to the presence of contingency factors, two of which are GCG and Leverage. This study aims to examine the effect of company size on tax avoidance with corporate governance and leverage as a moderator.  This research was conducted on mining and financial services companies listed on the Indonesia Stock Exchange for the period 2014-2018 there were 40 observations using data analysis techniques, namely the moderated regression analysis (MRA) test. The results of the study found that company size had a positive effect on tax avoidance. GCG can weaken the influence of company size on tax avoidance. Leverage can strengthen the effect of company size on tax avoidance. Keywords: Tax Avoidance; Size of Firm; GCG; Leverage.